Penambahan Vitamin C Pada Pengencer Spermatozoa Babi Landrace Yang Disimpan Pada Suhu 15ºC (ADDITION OF VITAMIN C IN DILUENT OF LANDRACE SPERM STORED IN TEMPERATURE OF 15ºC) - Bebas, Wayan; Budiasa, Made Kota; Astutik, Ika Yuni (Buletin Veteriner Udayana; Vol. 7 No. 2 Agustus 2015, 2015)
The aims of this study were to determine the viability and motility of Landrace pig’sspermatozoa in the Beltsville Thawing Solution (BTS) diluent with addition vitamin C which werestored at a temperature of 15ºC. During the storage process, metabolic activity of spermatozoaproduce free radicals that can reduce the viability and motility of spermatozoa thus it needs theaddition of antioxidants. Vitamin C is an antioxidant that can be used to scavengethe free radicals.This study used vitamin C added into the BTS diluent with scavenge dose is 0.1 mg/ml, 0.2 mg/mland a dose of 0.3 mg/ml. The results showed that a dose of 0.1 mg/ml is the best dose to maintainthe viability and motility of Landrace pigs spermatozoa were storage at a temperature of 15ºC.
Keywords: sperm, pig, vitamin C, viability, motility